Impact of Investment Choices, Dividend Strategy, and Operational Effectiveness on Financial Performance with Capital Structure Serving as a Control Variable - Laili Nur Romadhoni; Wuryaningsih Dwi Lestari (Program Pascasarjana STIE Amkop Makassar, 2026)
This research endeavors to evaluate the influence of investment decisions, dividend policies, and operational efficiency on the financial performance of manufacturing firms within the food and beverage sector that are publicly traded on the Indonesia Stock Exchange from 2021 to 2023, incorporating capital structure as a control variable. The secondary data utilized are derived from annual financial reports and are analyzed through the Random Effect Model (REM) methodology for panel data regression employing EViews 12 software. The results revealed that investment decisions and dividend policies had a notably adverse effect on financial performance, whereas operational efficiency demonstrated positive yet statistically insignificant effects. Collectively, all variables exhibited a significant impact with a coefficient of determination standing at 66.68%. These findings highlight the critical importance of adept management of investment decisions and dividend policies in sustaining corporate profitability.